Towards Adaptive Multipath Managing: A Lightweight Path Management Mechanism to Aid Multihomed Mobile Computing Devices - Cao, Yuanlong; Collotta, Mario; Xu, Siyi; Huang, Longjun; Tao, Xueqiang; Zhou, Zhichao (Applied sciences, 2020)
With the large scale deployment of multihomed mobile computing devices in today’s Internet, the Multipath TCP (MPTCP) is being considered as a preferred data transmission technology in the future Internet due to its promising features of bandwidth aggregation and multipath transmission. However, MPTCP is more likely to be vulnerable to the transmission quality differences of multiple paths, which cause a “hot-potato” out-of-order arrival of packets at the receiver side, and in the absence of a related approach to fix this issue, serious application level performance degradations will occur. In this paper, we proposes MPTCP-LM 3 , a Lightweight path Management Mechanism to aid Multihomed MPTCP based mobile computing devices towards efficient multipath data transmission. The goals of MPTCP-LM 3 are: (i) to offer MPTCP a promising path management mechanism, (ii) to reduce out-of-order data reception and protect against receiver buffer blocking, and (iii) to increase the throughput of mobile computing devices in a multihomed wireless environment. Simulations show that MPTCP-LM 3 outperforms the current MPTCP schemes in terms of performance and quality of service.